Encyclopedia of philosophy - Borchert, Donald M., 1934- (Detroit : Thomson/Gale, 2006)
Presents a collection of alphabetically-arranged entries that provide information on a wide range of topics related to philosophy, including ethics, religion, history, aesthetics, logic, metaphysics, from Aristotle and the Greek Academy, to modern concepts of feminist theory and philosophy of the mind.
Vol. 1. Abbagnano-Byzantine philosophy -- v. 2. Cabanis-Destutt de Tracy -- v. 3. Determinism-Fuzzy logic -- v. 4. Gadamer-Just war theory -- v. 5. Kabbalah-Marxist philosophy -- v. 6. Masaryk-Nussbaum -- v. 7. Oakeshott-Presupposition -- v. 8. Price-Sextus empiricus -- v. 9. Shaftesbury-Zubiri -- v. 10. Appendix, thematic outline, bibliographies, index.
Includes bibliographical references and index.
Booklist starred.
Choice.
Library Journal.
Adult
Keywords: Philosophy -- Encyclopedias; Philosophy -- Encyclopedias